Prefácio e Organização - Soares Neto, Carlos de Salles; Macedo, Alessandra Alaniz (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
Este documento traz o Prefácio e a Organização dos Anais do WebMedia 2025.